2020
DOI: 10.1371/journal.pone.0233122
|View full text |Cite
|
Sign up to set email alerts
|

The Childbirth Experience Questionnaire (CEQ)—Validation of its use in a Danish-speaking population of new mothers stimulated with oxytocin during labour

Abstract: Background When determining optimal treatment regimens, patient reported outcomes including satisfaction are increasingly appreciated. It is well established that the birth experience may affect the postnatal attachment to the newborn and the management of subsequent pregnancies and deliveries. As we have no robust validated Danish tool to evaluate the childbirth experience exists, we aimed to perform a transcultural adaptation of the Childbirth Experience Questionnaire (CEQ) to a Danish context. Methods In ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
7
22
2
1
Order By: Relevance
“…In our results, the final mode of delivery proved to be significant in the domains of Professional support, Perceived safety, Participation, and overall CEQ score. Women with spontaneous vaginal delivery reported lower satisfaction, which differs from the results of Boie et al (2020), andDencker et al (2010), who found that women with spontaneous delivery were more satisfied with childbirth. In our study, the final mode of childbirth was significant in the Perceived safety domain in women after surgical delivery, who reported lower satisfaction with childbirth.…”
Section: Discussioncontrasting
confidence: 88%
“…In our results, the final mode of delivery proved to be significant in the domains of Professional support, Perceived safety, Participation, and overall CEQ score. Women with spontaneous vaginal delivery reported lower satisfaction, which differs from the results of Boie et al (2020), andDencker et al (2010), who found that women with spontaneous delivery were more satisfied with childbirth. In our study, the final mode of childbirth was significant in the Perceived safety domain in women after surgical delivery, who reported lower satisfaction with childbirth.…”
Section: Discussioncontrasting
confidence: 88%
“…The childbirth experience is a complicated mental concept with various dimensions [1]. Evaluation of the childbirth experience using a standard scale which has been used in different countries is the other strength of the current study [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Item ratings are aggregated to scale scores by summing the coded values of the items in each scale and dividing by the number of items in that scale; higher scores indicate a more positive childbirth experience [20, 21]. Based on the Terwee’s criteria (a quality criteria’s checklist for measurement properties of health field scales), the CEQ-2 psychometric properties quality score has been shown to be a suitable tool for clinical studies [25] and it has been translated into many languages such as Spanish [26], Malaysian [27] and Danish [28].…”
Section: Introductionmentioning
confidence: 99%